Social Media and Examination Malpractice among Senior Secondary Certificate Examination (SSCE) Candidates in Gombe State - Abubakar,, M.; Vincent,, Y. I. (Kashere Journal of Education, 2021)
The effect of social media towards learning cannot be over-emphasized but notwithstanding the bad side of it, is also prevalent amongst students. It is against this background that this study is aimed at investigating the relationship between examination malpractice and social media. The research design used was survey research with Quantitative method and Descriptive statistics used for both gathering the data and data analysis, respectively. The objectives of the study were to investigate whether SSCE candidates use social media to engage in examination misconduct and the difference between the use of social media for examination misconduct amongst male and female candidates. The study revealed that SSCE candidates use social media for examination malpractice and it also found out that the male candidates use social media for examination malpractice more than their female counterparts. The researchers recommended that proper checking of candidates by invigilators be done to ensure that no candidate gets into examination hall with any electronic device and examination centres which are dominated by male candidates should be assigned more invigilators.